PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DISIPLIN KERJA, DAN BURNOUT PADA KINERJA KARYAWAN ARMA MUSEUM AND RESORT - Mahendra, Kadek Manik Oko; Mujiati, Ni Wayan (E-Jurnal Manajemen, 2015)
The purpose of this study was to analyze 1) the influence of transformational leadership on employee performance. 2) the effect of labor discipline on employee performance. 3) the effect of burnout on employee performance. This research was conducted on employees Arma Museum and Resort, samples taken as many as 52 people. Data collection is done 9 by observations, 9 interviews, and questionnaires t . Data analysis technique used is multiple linear regression analysis, the model accuracy test (Test F), and the t test. Results of the data analysis showed that the variables of leadership transfromational positive and significant impact on the performance of employees, work discipline variable positive and significant effect on the performance of the employee, while the variable burnout significant negative effect on the performance of the employee. This research suggestion, the leader should always give encouragement or motivation to employee, management should be more assertive and did not hesitate to impose sanctions on employees who violate the rules, and the management provide additional hours of resting, so that employees are not exhausted in doing his job.
Keywords: kepemimpinan transformasional; disiplinikerja; burnout; kinerja